Authentic Dialogue: The Communication of Collaborative Leadership - Wright, Jorja (Advances in Social Sciences Research Journal, 2017)
Our society has become very complexed and the amount of wicked problems has also increased. Diverse and creative thinking, accompanied by affective leadership, are necessary to reduce the symptoms of healthcare inequities, educational disparities, and climate change. Collaboration is a synergistic process that aims to benefit the group exponentially once all stakeholders work together effectively to reach mutual goals. Authentic dialogue is defined as open and honest conversations that abide by the Habermas speech conditions in which fair exchanges of thoughts lead to detecting and correcting errors (or reconciling differences) amongst engaged actors. This paper: (a) defines authentic dialogue and the conditions for this concept to be used effectively; (b) explains collaborative leadership through the diversity, interdependence, authentic dialogue (DIAD) theory, (c) articulates why understanding systems theory will aid leaders in developing better communication skills; (d) concludes with possible limitations and further studies needed about authentic dialogue within the collaborative process. Key words: Collaborative leadership, authentic dialogue, complexity, systems theory